1984
DOI: 10.1111/j.1365-2621.1984.tb10433.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Components of Mushroom (Agaricus subrufecens)

Abstract: Volatile components of mushroom (Agaricus subrufecens) were extracted by the simultaneous distillation-extraction method. About 30 volatile components could be identified by GC and K-MS analyses. Aromatic compounds, such as benzyl alcohol, benzaldehyde, benzonitrile, methyl bcnzoate, and a phenyl acetic acid-like compound, were the major volatiles (>85%) and are possibly the cause of "almond-like" aroma of this mushroom. Eight carbon compounds which are common to most mushroom volatiles make up only a minor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
0
16
0
4
Order By: Relevance
“…The identification of volatile compounds was based on computer matching with the mass spectra in the NIST 05, WILEY and ADAMS libraries, as well as by comparison of the mass spectra and retention indices (RI) according to those reported in the literatures [1,[10][11][12][13][14][15][16][17][18][19]23]. In addition, a home-made library in the Shanghai Institute of Technology, based on the analysis of reference oils and commercially available standards, was also used for the identification and quantification.…”
Section: Identification and Quantification Of Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of volatile compounds was based on computer matching with the mass spectra in the NIST 05, WILEY and ADAMS libraries, as well as by comparison of the mass spectra and retention indices (RI) according to those reported in the literatures [1,[10][11][12][13][14][15][16][17][18][19]23]. In addition, a home-made library in the Shanghai Institute of Technology, based on the analysis of reference oils and commercially available standards, was also used for the identification and quantification.…”
Section: Identification and Quantification Of Volatile Compoundsmentioning
confidence: 99%
“…It was suggested that the aldehydes of 5-methyl-2-phenyl-2-hexenal, benzaldehyde, and phenyl acetaldehyde were generated from the Maillard reaction pathway [33]. Chen and Wu [16] also demonstrated the presence of 5methyl-2-phenyl-2-hexenal in mushroom of Agaricus subrufescens. Volatile compounds of aldehydes generally displayed coarse and heavy aromas of raw fish [34].…”
Section: Volatile Compounds In Differentmentioning
confidence: 99%
“…On the other hand, octen-3-ol was not found in the solvent extract of M. alliaceus even if it was very often reported in mushrooms (Dijkstra and Wikén, 1976;Pyysalo and Suihko, 1976;Chen and Wu, 1984;Vidal et al, 1986;Mau et al, 1992;Buchbauer et al, 1993).…”
Section: Resultsmentioning
confidence: 92%
“…Compound 35 is identified as 2,3,4,6-tetrathiaheptane due to the presence of m/z 93 and 79 fragments; the value of the chromatographic retention index of 35 is coherent with those of the previous sulfur compounds. Compound 41 with molecular mass 218 and five sulfur atoms should be the superior homologue of 35; the structure of On the other hand, the first three dimethyl polysulfides 10, 22, and 32 were identified in M. alliaceus as reported in Lentinus edodes (Morita and Kobayashi, 1966;Chen and Wu, 1984;Chen and Ho, 1986), cheeses (Cuer et al, 1979), Allium species, i.e., onions (Kuo and Ho, 1992) and leeks (Stephani and Baltes, 1992), and brassicaceous vegetables (Maruyama, 1970). 1,2,4-Trithiolane (27), which was found in high level in L. edodes (Chen and Ho, 1986), was detected in very low amount in M. alliaceus; compound 27 was identified by the retention index value and mass spectrum, which were similar to those reported by Chen and Ho (1986).…”
Section: Resultsmentioning
confidence: 98%
“…Este método se ha aplicado a muchos alimentos: quesos (Aishima, 1987), setas (Chen, 1984), peras (Russell, 1981), jugo de pomelo (Núñez, 1985), pepino (Shioía, 1988), pericarpo de melón (Horvat, 1987), uvas (Horvat, 1984), pistachos (Wyllie, 1990), tes (Owuor, 1990), etc.…”
Section: Destilación-extracción Simultáneaunclassified